2017
DOI: 10.1364/ol.42.003197
|View full text |Cite
|
Sign up to set email alerts
|

Optical frequency combs generated mechanically

Abstract: An elongated bottle microresonator with nanoscale parabolic effective radius variation can possess a series of dense equally spaced optical eigenfrequencies whose separation can match the eigenfrequency of its axially symmetric acoustic mode. It is shown that this acoustic mode can parametrically excite optical modes and give rise to a highly equidistant and moderately broadband optical frequency comb with the teeth spacing independent of the input laser power and the amplitude of mechanical vibrations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Remarkably, the characteristic length of the acoustic modes with the same axial quantum number is much greater than that for the optical modes. [78,79]).…”
Section: Optomechanics Of Bmrsmentioning
confidence: 99%
See 2 more Smart Citations
“…Remarkably, the characteristic length of the acoustic modes with the same axial quantum number is much greater than that for the optical modes. [78,79]).…”
Section: Optomechanics Of Bmrsmentioning
confidence: 99%
“…Fig. 17 It was shown that the BMR with gigantic axial radius of the order of 1 km can be designed so that its mechanical eigenfrequency matches the separation of its optical eigenfrequencies along the axial quantum number [78,79]. Since the axial free spectral range of acoustic modes is very small, it is desirable for this application to remove all acoustic modes except for the fundamental axial mode (black line in Fig.…”
Section: Optomechanics Of Bmrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using nonlinear effects other than Kerr nonlinearity for comb generation is an active research area. One can mention here examples of the comb generation due to cascaded Raman and Brillouin effects [3][4][5][6], polariton [7,8] and graphene nonlinearities [9], and quadratic, χ (2) , nonlinear effects [10][11][12][13][14][15][16][17][18][19][20][21][22]. The latter hold a particular promise.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the nonlinear dynamics of optomechanical cavities has been intensively explored in the recent literature, while various static and dynamics aspects, such as bistability [26][27][28], spontaneous symmetry breaking [29], self-induced oscillations [30][31][32][33], and chaos [34][35][36] have been investigated. In addition, parametric generation of equally spaced optical lines induced by the acoustic modes in bottle microresonators have also been explored [37]. Even though parametric self-sustained mechanical oscillations have been well studied in this context, no significant effort has been made to analyze and tailor the formation of frequency combs in optomechanical systems.…”
Section: Introductionmentioning
confidence: 99%